2021
DOI: 10.2174/1871530320666200604161656
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gasdermin A, Gasdermin B Polymorphisms and Allergic Rhinitis Amongst Jordanians

Abstract: Introduction: Gasdermin A (GSDMA) and Gasdermin B (GSDMB) have been associated with childhood and to a lesser extent with adult asthma in many populations. In this study, investigate whether there is an association between GSDMA (rs7212938, T/G) and GSDMB (rs7216389, T/C) at locus 17q21.2 and risk of Allergic Rhinitis among Jordanians. Also we aimed to determine if there is an association between such polymorphisms and the IgE level. Methods: The study included 112 rhinitis patients and 111 Healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Rs10852936 is located in a long-range chromatin interaction region, which includes genes IKZF3, ZPBP2, GSDMB, and ORMDL3. Through the review of previous literature, we found that genes IKZF3, ZPBP2, GSDMB, and ORMDL3 were expressed in lymphocytes, and were significantly associated with the onset of inflammatory and immune diseases such as juvenile asthma [5], Crohn's disease [6] and rheumatoid arthritis [7]. These diseases share some common pathogenesis with psoriasis, which is also an inflammatory and immune disease.…”
Section: Introductionmentioning
confidence: 96%
“…Rs10852936 is located in a long-range chromatin interaction region, which includes genes IKZF3, ZPBP2, GSDMB, and ORMDL3. Through the review of previous literature, we found that genes IKZF3, ZPBP2, GSDMB, and ORMDL3 were expressed in lymphocytes, and were significantly associated with the onset of inflammatory and immune diseases such as juvenile asthma [5], Crohn's disease [6] and rheumatoid arthritis [7]. These diseases share some common pathogenesis with psoriasis, which is also an inflammatory and immune disease.…”
Section: Introductionmentioning
confidence: 96%